Critical considerations on the traditional syllabus of the subject Internal Medicine - Ángel Julio Romero Cabrera (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Internal Medicine is a specialty of wide profile which has always supported the best qualities of clinics. The syllabus of this subject, which rules the Chair of Medical Clinics (traditional syllabus) dates back to 1989 and, even when there could be some invariants regarding methods and objectives, many things have also changed in these years and it is important to perform modifications, particularly in its content. Thus, it is necessary to update the syllabus to adequate it to the requirements and events above mentioned, without transforming its core mission of educating a general comprehensive doctor with humanistic and social scope. The objective of this article was to critically analyze some aspects that can not be omitted if we want to foster a subject based in a comprehensive specialty as Internal Medicine.